2013
DOI: 10.1002/adem.201300096
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of Silicon Phase Morphology on the Microstructural Stress Distribution in Al–Si Alloys Using Object Oriented Finite Element Modeling

Abstract: Near‐eutectic Al–Si alloys were produced by conventional casting and spray forming resulting in microstructural differences due to process dependent cooling rates. The as‐sprayed alloy exhibited fine equiaxed Si particles uniformly distributed throughout the matrix in contrast to the as‐cast alloy, which exhibited acicular morphology with relatively large needle‐like Si particles. The effect of Si morphology on the microstructural stress distribution of the as‐cast and as‐sprayed alloys was estimated by simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The various phases in the microstructure are identified by image analysis and appropriate material properties (Young's modulus and Poisson's ratio) are assigned to each of the phases followed by creating the mesh and applying the boundary conditions. In the present study, hypothetical microstructures representing the real microstructures of Al-Si alloys of various silicon particle sizes and shape were used and subjected to uni-axial tensile loading conditions using the procedure as explained by Raghukiran et al [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The various phases in the microstructure are identified by image analysis and appropriate material properties (Young's modulus and Poisson's ratio) are assigned to each of the phases followed by creating the mesh and applying the boundary conditions. In the present study, hypothetical microstructures representing the real microstructures of Al-Si alloys of various silicon particle sizes and shape were used and subjected to uni-axial tensile loading conditions using the procedure as explained by Raghukiran et al [14].…”
Section: Methodsmentioning
confidence: 99%
“…But all the spray deposits in the present study have shown similar wear resistance at the lower normal loads while alloys with higher silicon content have shown better wear performance at relatively higher normal pressures. It was reported that at relatively lower normal pressures, there was no much influence of the amount of silicon in the alloy [14]. This was attributed to the formation of oxide layer due to the built up of temperature that is relatively stable under smaller loads.…”
Section: Wear Performancementioning
confidence: 97%
See 1 more Smart Citation